Pencegahan Covid-19 Melalui Sosialisasi Penggunaan Dan Pembagian Masker Di Kota Tasikmalaya Dan Kabupaten Tasikmalaya - Irma Nuraeni; Raden Agus Bachtiar; Ima Karimah Karimah; Naning Hadiningsih; Dina Setiawati; Marianawati Saragih (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Coronavirus Disease 2019 (Covid-19) is an infectious disease whose development is very fast and has become a pandemic in several countries, including Indonesia. The use of masks is one of the efforts recommended by WHO to prevent the spread of Covid-19. The purpose of this community service was to increase knowledge through socializing the use of masks and distributing 2000 of 3-ply masks to community in Tasikmalaya City and Tasikmalaya Regency in September 2020. This activity went smoothly and without a hitch. The community response was quite good, very open and enthusiastic. This activity was very useful, especially for people whose activity in public areas such as markets and sports fields. It is hoped that it will be sustainable and need for periodic monitoring with wider range to prevent the spread of Covid-19.